Comparative evaluation of adequacy of final working length after using Raypex5 or radiography: An in vivo study - Deepika Singh; Shashi Prabha Tyagi; Swati Gupta; Ankita Jain (Wolters Kluwer Medknow Publications, 2015)
Aim: The aim of this clinical study was to compare the effect of working length (WL) determination using electronic apex locator (EAL) or WL radiograph on the length adequacy of final WL. Materials and Methods: A total of 153 patients with 153 teeth with single canal were randomized into two groups; in Group 1, the WL was determined by WL radiograph; whereas in Group 2, it was determined by the Raypex5 EAL (VDW, Munich, Germany). Length adequacy was assessed in each group for master cone and categorized into short, acceptable, and over cases. Statistical Analysis Used: The data were statistically analyzed using the Pearson chi-square test at a significance level of P < 0.05. Results: There was no statistically significant difference between the groups in the rates of acceptable (Group 1 = 83.1% and Group 2 = 92.1%) and short cases (Group 1 = 3.9% and Group 2 = 5.2%). Over cases in master cone radiography were significantly more in Group 1 (13.1%) than Group 2 (2.6%) (P = 0.017). Conclusion: The results of our study have shown that under clinical condition, success of Raypex5 was comparable to the radiographic WL determination technique in terms of acceptable and short cases. However, there were significantly lesser over cases in EAL group, showing that EALs can avoid the overestimation of WL.